Pemanfaatan Bank Sampah Untuk Meningkatkan Perekonomian Masyarakat di Bank Sampah Anyelir - Siregar, Ratih Anggraini (Servitium Smart Journal, 2024)
Garbage is an environmental and urban community problem that until now has no solution. The limited number of landfills (TPA) in Medan City makes this waste problem even more complex. The waste bank is an alternative in the waste management strategy. The waste bank is one of the programs that can change the pattern of people's views on waste management. This community service program is located at the Carnation Garbage Bank. Some of the problems that exist with partners include Partners have basic problems such as lack of knowledge about the dangers of waste and waste management/sorting and lack of knowledge about waste banks, how they work, and generate income just by sorting and depositing them to the waste bank. The approach method that will be carried out based on an agreement with partners is by socializing about waste and its management, and how housewives can earn income from existing waste management. The expected output is the community is educated to sort waste and deposit waste to the Garbage Bank, to create a clean and healthy environment. It is hoped that the role of the Medan City Government in the establishment of this waste bank.